DEKONSTRUKSI HUBUNGAN KEAGENAN DALAM PROSES ANGGARAN - Ratna Ayu Damayanti; Syarifuddin Syarifuddin (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2021)
Purpose – The study objective are to explore the importance of local wisdom as a source of knowledge and guidance in filling and forming a more harmonious agency relationship pattern in the context of local government budgets. Design/methodology/approach – This study uses Derrida model. Findings – This study finds out how modern the accountability system of traditional Balinese village. In this case, budget is not only for legislative consumption, but also for all levels of society. Failure to provide accountability report by customary government is a form of violation that causes karma, and villager can revoke the mandate given to the customary government. Originality – This study uses Derrida model to build a new model of agency relationship by adopting marginalized text or philosophical. Keywords: Bali, Derrida, Budget, Regional Government, Indonesia Paper Type Research Result